(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2025)
The relationship between the right to mental health and neurotechnologies has not been properly explored yet. This paper replies to the following research questions: a) Can the right to mental health benefit from neurotechnologies?; and b) How does the right to mental health take shape in the context of this kind of technology? We demonstrate that neurotechnologies can contribute to the realisation of the right to mental health. Techniques such as deep brain stimulation, neuroimaging and mobile apps can help prevent and treat mental disorders. In addition, we examine how the right to mental health applies in the field of neurotechnologies. In so doing, we present concrete obligations of the State in this regard.